(untitled) (Acta Scientiarum. Health Sciences, 2013)
The mammalian testis is a complex organ with endocrine and exocrine functions. It consists of seminiferous tubules where the production of the male gametes called spermatogenesis occurs. This process is influenced by a number of factors including the use of physical performance-enhancing drugs. The objective of this study was to evaluate the effects of the anabolic steroid nandrolone decanoate on the morphofunctional structure of testes in sedentary rats and rats subjected to moderate aerobic exercise training. Twenty-four male rats were divided into four experimental groups: sedentary control, sedentary treated, trained control and trained treated.The training lasted eight weeks and consisted of running on a programmable ergometer treadmill, tailored to train eight rats simultaneously. Treated animals received intramuscular injections of nandrolone decanoate (0.5 mg kg-1 body weight) during the last four weeks of physical training, while the control groups received intramuscular injections of vehicle (vegetable oil).The male reproductive system morphology showed that treatment with nandrolone decanoate, in both sedentary and trained rats, promoted morphological and functional changes that result in reduced efficiency of spermatogenesis.